Non-invasive assessment of periodontal inflammation by continuum-removal hemodynamic spectral indices - Guo, Yuan; Huang, Yixiang; Huang, Changping; Sun, Xuejian; Luan, Qingxian; Zhang, Lifu (European journal of medical research, 2024)
Hyperspectral techniques have aroused great interest in non-invasively measuring periodontal tissue hemodynamics. However, current studies mainly focused on three typical inflammation stages (healthy, gingivitis and periodontitis) and practical approaches for using optical spectroscopy for early and precisely detection of periodontal inflammation at finer disease stages have not been well studied. This study provided novel spectroscopic insights into periodontitis at different stages of disease, and developed six simple but physically meaning hemodynamic spectral indices (HSIs) including four spectral absorption depths of oxyhemoglobin ( ), deoxyhemoglobin ( ), total hemoglobin ( ) and tissue water ( ), and two normalized difference indices of oxyhemoglobin( ) and deoxyhemoglobin ( ) from continuum-removal spectra (400-1700 nm) of periodontal tissue collected from 47 systemically healthy subjects over different severities from healthy, gingivitis, slight, moderate to severe periodontitis for early and precision diagnostics of periodontitis. Typical statistical analyses were conducted to explore the effectiveness of the proposed HSIs. and exerted significant increasing trends as inflammation progressed, whereas exhibited significant difference (P < 0.05) from the healthy sites only at moderate and severe periodontitis and presented unstable sensitives to disease severity. By contrast, and showed more steadily downward trends as severity increased, and demonstrated the highest correlations with clinical gold standard parameters. Particularly, the proposed normalized HSIs ( and ) yielded high correlations of - 0.49 and - 0.44 with probing depth, respectively, far outperforming results achieved by previous studies. The performances of the HSIs were also confirmed using the periodontal therapy group. These results indicated great potentials of combination optical spectroscopy and smart devices to non-invasively probe periodontitis at earlier stages using the simple and practical HSIs. Trial registration This study was retrospectively registered in the Chinese Clinical Trial Registry on October 24, 2021, and the clinical registration number is ChiCTR2100052306.